2017
DOI: 10.1007/s00464-017-5971-5
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of upstage diagnosis after endoscopic resection of gastric low-grade dysplasia

Abstract: This study identified several risk factors that were significantly associated with the upstage diagnosis of gastric low-grade dysplasia: lesion size ≥ 10 mm and a variety of surface changes (erythema, nodularity, depression, and erosion). Our data indicate that if there is no evidence of these endoscopic risk factors, then regular follow-up may be considered, according to the patient's combined comorbid conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 18 publications
3
25
1
Order By: Relevance
“…Downgrading LGD lesions was also reported after endoscopic resection, with the rate ranging from 0.8% to 4.5% . In our study the downgrade rate of the pathological diagnosis was 12.5%, which is higher than that in the published data.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations
“…Downgrading LGD lesions was also reported after endoscopic resection, with the rate ranging from 0.8% to 4.5% . In our study the downgrade rate of the pathological diagnosis was 12.5%, which is higher than that in the published data.…”
Section: Discussioncontrasting
confidence: 70%
“…The abovementioned data show that the risk of biopsy‐diagnosed LGD lesions to progress to invasive cancers is low, and most LGD lesions regress to gastritis or show no histological change. However, accumulated evidence has shown that the rates of progression from biopsy‐diagnosed LGD to HGD or gastric adenocarcinoma after endoscopic resection are higher, ranging from 12.1% to 63% . In our study, the upgrade rates of LGD to HGD or adenocarcinoma were as high as 48.9%, indicating the need for the aggressive management of biopsy‐diagnosed LGD.…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Previous studies have reported that 12.1% to 63% of LGD lesions are upgraded to HGD or GC after ER. [5][6][7][8][9][10][11][12][13][14][15] In addition, gastric HGD has been shown to be GC in about 27% to 80% of cases after ER. [16][17][18] In this study, we aimed to evaluate the clinical outcomes of ER for gastric LGDs and HGDs on pretreatment FB, using the multicenter large-scale endoscopic submucosal dissection (ESD) registry database.…”
Section: Introductionmentioning
confidence: 99%